Numerical investigation of heat transfer and pressure drop of water-nanofluid flow in a three-dimensional wavy mini-tube - Mohammad Rahimi Baghbadorani; Omid Ali Akbari (International Journal of Thermofluids)
This research employs three-dimensional simulations to investigate the behavior of pure water and nanofluids consisting of Al2O3 and TiO2 particles within a sinusoidal mini-tube as a single-phase suspension. The impact of a mini-tube's sinusoidal amplitude and wavelength on laminar flow properties is investigated in Reynolds numbers ranging from 100 to 600. The results present that performance evaluation criterion of mini-tube is more proper in the amplitude of 3 mm and wave length of 16 mm. Performance evaluation criterion of sinusoidal shaped mini-tube with pure water in comparison with straight mini-tube, shows that sinusoidal mini-tube has the proper performance which the performance evaluation criterion is greater than 1. Proper selected mini-tube is also used with nanofluids. In this simulation, proposed nanofluids are water-Al2O3 and water-TiO2 nanofluids with volume fractions of 2 % and 4 %. The results of this investigation reveal that using nanofluids improves performance evaluation criterion. Also, comparison of two different nanoparticles shows that Al2O3 nanoparticles have better performance in comparison with TiO2 nanoparticles. By changing geometrical parameters as amplitude and wave length and finding proper mini-tube, it is seen that performance evaluation criterion is increased two times in comparison with straight tube. Also, using nanofluid in proper mini-tube in comparison with pure water in the same mini-tube, leads to improvement of cooling and thermal performance up to of 20 %, in the different Reynolds numbers.